Model Matematika Penyebaran Covid-19 Dengan Karantina Dan Vaksinasi - Hukmah HUkmah; Muhammad Rifki Nisardi; Sulma Sulma; Suriani M (Department of Mathematics, Hasanuddin University, 2023)
Abstract We present a mathematical model of COVID-19 disease by modifying the SEIR model. The model considers two additional compartments, quarantine (Q) and vaccination (V) which aim to control the spread of COVID-19. Based on the model, we obtained a disease-free equilibrium point and an endemic equilibrium point. The basic reproduction numbers were calculated using the next-generation matrix method. In this model, we analyzed the stability conditions that must be satisfied by the defining parameters. We perform data on the spread of COVID-19 in Indonesia for estimation to provide the parameter value in the model. Based on the result, there is an influence of changes in several parameter values on the number of individuals infected with COVID-19.